2020
DOI: 10.1002/uog.20380
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of Doppler reference charts on management of small‐for‐gestational‐age fetuses: need for standardization

Abstract: Objective To assess clinical variability in the management of small‐for‐gestational‐age (SGA) fetuses according to different published Doppler reference charts for umbilical artery (UA) and fetal middle cerebral artery (MCA) Doppler indices and cerebroplacental ratio (CPR). Methods We performed a systematic search of MEDLINE, EMBASE, CINAHL and the Web of Science databases from 1954 to 2018 for studies with the sole aim of creating fetal Doppler reference values for UA, MCA and CPR. The top cited articles for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 48 publications
1
18
0
2
Order By: Relevance
“…Even among studies with a high methodological quality score, there are significant differences in the definition of 'normality' and normal ranges 46 . A recent study evaluating the 10 most-cited articles providing reference ranges for MCA-PI, UA-PI and cerebroplacental ratio (CPR), found wide discrepancies in Doppler reference values that accounted for a variability of up to 50% in the 5 th percentile cut-off value of MCA-PI at term 47 . Similarly, the study found significant differences in the cut-off for UA-PI above the 95 th percentile (20-40%) and CPR below the 5 th percentile (15-35%) 47 .…”
Section: Doppler Velocimetrymentioning
confidence: 99%
See 2 more Smart Citations
“…Even among studies with a high methodological quality score, there are significant differences in the definition of 'normality' and normal ranges 46 . A recent study evaluating the 10 most-cited articles providing reference ranges for MCA-PI, UA-PI and cerebroplacental ratio (CPR), found wide discrepancies in Doppler reference values that accounted for a variability of up to 50% in the 5 th percentile cut-off value of MCA-PI at term 47 . Similarly, the study found significant differences in the cut-off for UA-PI above the 95 th percentile (20-40%) and CPR below the 5 th percentile (15-35%) 47 .…”
Section: Doppler Velocimetrymentioning
confidence: 99%
“…A recent study evaluating the 10 most-cited articles providing reference ranges for MCA-PI, UA-PI and cerebroplacental ratio (CPR), found wide discrepancies in Doppler reference values that accounted for a variability of up to 50% in the 5 th percentile cut-off value of MCA-PI at term 47 . Similarly, the study found significant differences in the cut-off for UA-PI above the 95 th percentile (20-40%) and CPR below the 5 th percentile (15-35%) 47 . Wide discrepancies have been reported in reference ranges used for biometry, Doppler parameters and birth weight, even at national level in centers with high expertise in the management of FGR, that might significantly impact the diagnosis and management of FGR 48 .…”
Section: Doppler Velocimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Durante la evaluación de este artículo, Ruiz Martínez (17) publicó un estudio similar que compara el percentil 95 del IP AU de 19 publicaciones diferentes, encontrando variación entre 20 y 40% de este valor crítico entre ellas, a lo largo del embarazo.…”
Section: Discussionunclassified
“…This uncertainty may at least in part be due to the heterogeneity of reference charts for fetal arterial Doppler parameters 16 , and part of this, but not all, could be explained by methodological shortcomings. Ruiz-Martinez et al performed a simulation analysis in a cohort of small for gestational age (SGA) fetuses using percentile thresholds from 10 most frequently cited arterial Doppler reference charts (UA-PI, MCA-PI and CPR) 17 . They concluded that the variation in percentile thresholds could result in a large variation in clinical management.…”
Section: Introductionmentioning
confidence: 99%